2016
DOI: 10.1016/j.neuropsychologia.2016.05.019
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between auditory cognition and speech intelligibility in cochlear implant users: An ERP study

Abstract: There is a high degree of variability in speech intelligibility outcomes across cochlear-implant (CI) users. To better understand how auditory cognition affects speech intelligibility with the CI, we performed an electroencephalography study in which we examined the relationship between central auditory processing, cognitive abilities, and speech intelligibility. Postlingually deafened CI users (N=13) and matched normal-hearing (NH) listeners (N=13) performed an oddball task with words presented in different b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
107
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 80 publications
(145 citation statements)
references
References 71 publications
26
107
3
1
Order By: Relevance
“…According to this model, one would hypothesize that verbal abilities relate to late event-related potential (ERP) components as well as to the speech intelligibility outcome with the CI . This idea has been supported by our previous study which revealed that the N2/N4 latency of CI users was related to speech perception scores as well as to the subjective listening effort ratings in these individuals [Finke et al, 2016]. However, the previous results have been obtained with bilaterally and bimodally fitted CI users.…”
Section: Introductionsupporting
confidence: 54%
See 4 more Smart Citations
“…According to this model, one would hypothesize that verbal abilities relate to late event-related potential (ERP) components as well as to the speech intelligibility outcome with the CI . This idea has been supported by our previous study which revealed that the N2/N4 latency of CI users was related to speech perception scores as well as to the subjective listening effort ratings in these individuals [Finke et al, 2016]. However, the previous results have been obtained with bilaterally and bimodally fitted CI users.…”
Section: Introductionsupporting
confidence: 54%
“…Participants were tested with an auditory oddball paradigm with a target probability of 20% [Finke et al, 2016;Polich, 2007]. Each trial consisted of a disyllabic German noun (800 ms long), and participants had to identify it as a living or nonliving entity ( Fig.…”
Section: Task and Proceduresmentioning
confidence: 99%
See 3 more Smart Citations